The Effectiveness of Teaching Emotion Management Strategies Based on the Emotionally-Focused Couple Therapy Approach in Improving Family Functioning and Marital Satisfaction - Birak, Fatemeh; Dokanehi Fard, Farideh; Jahangir, Pantea (Applied Family Therapy Journal (AFTJ), 2022)
Aim: The present study aimed to determine the effectiveness of teaching emotion management strategies based on the emotionally-focused couple therapy approach in improving family functioning and marital satisfaction. Methods: The research was semi-experimental and had a pretest-posttest design with a control group and a two-month follow-up. Its statistical population consisted of 47 conflicting couples who visited counseling centers in Tehran in 2021. After screening by the McMaster Model of Family Functioning (1950) and ENRICH Marital Satisfaction Scale (EMS) (1998), 32 couples were selected by the convenience sampling method and were randomly assigned to the experimental group (16 couples) and the control group (16 couples). The experimental group received the intervention of emotion management strategies based on Johnson’s Emotionally-Focused Therapy (EFT) (2004) approach for eight 90-minute sessions, but the control group did not receive any intervention. Data were analyzed using the repeated-measures mixed-model analysis of variance (ANOVA). Results: The results indicated the effect of the emotion management strategies intervention based on the emotionally-focused couple therapy approach on the family functioning score (F=15.78, P=0.001) and marital satisfaction (F=15.16, P=0.001), and the stability of this effect was at the follow-up stage. Conclusion: The research results suggested evidence that the emotion management strategies intervention based on the emotionally-focused couple therapy approach was a suitable method to increase marital satisfaction and improve family functioning in couples with marital conflict.